Reliability of the ADI-R: multiple examiners evaluate a single case. - Cicchetti DV; Lord C; Koenig K; Klin A; Volkmar FR (Journal of Autism & Developmental Disorders, 2008)
The authors assessed the reliability of the Autism Diagnostic Interview (ADI-R). Seven Clinical Examiners evaluated a three and one half year old female toddler suspected of being on the Autism Spectrum. Examiners showed agreement levels of 94-96% across all items, with weighted kappa (K(w)) between .80 and .88. They were in 100% agreement on 74% of the items; in excellent agreement on 6% of the items (93-96%, with K(w) between .78 and .85); in good agreement on 7% (89-90%, with K(w) between .62 and 0.68); and in fair agreement on 3% (82 - 84%, with K(w) between .40 and .47). For the remaining 10% of ADI-R items, examiners showed poor agreement (50-81% with K(w )between -.67 and .37).